Comparison of medical students' considerations in choosing a specialty: 2020 vs. 2009/10 - Hanna Schroeder; Alon Shacham; Shimon Amar; Charles Weissman; Josh E. Schroeder (Human Resources for Health, 2024)
Abstract Background Workforce shortage in healthcare and particularly in physicians poses a threat to healthcare delivery and its quality. In comparison to other OECD countries, Israel currently has a small number of medical graduates relative to its number of physicians, naturally emphasizing the importance of ensuring that this population chooses to remain in medicine. Understanding what is most important to medical students can help improve working conditions in residency. Such information is particularly needed to facilitate policy planning that will encourage the next generation of physicians to specialize in medical fields that are experiencing shortages. We hypothesized that between 2009/2010 and 2020, there were significant changes in medical students' preferences regarding their considerations for choosing a medical specialty. Methods We compared cross-sectional data from questionnaire-based surveys of 5th year medical students performed in 2009–2010 and 2020 at two Israeli universities. Results Of the 335 medical students who responded (237 and 98 in 2009/2010 and 2020, respectively) those in 2020 were 2.26 less likely vs. those in 2009/2010, to choose a residency for its high-paying potential (P < 0.05), and had significantly more interest in residencies with greater teaching opportunity (98.8% vs 82.9%, P < 0.05), increased responsibility and chances to make clinical decisions on their own (67.9% vs 51.6%, P < 0.05). Criteria important to both the 2009/2010 and 2020 students were choosing a bedside specialty (70.2%vs 67.9%, NS), and an interesting and challenging specialty (95.2%v s 91.3%, NS). Conclusions These results partially supported our hypothesis that medical students' preferences have changed over the years, though there are fundamental factors that apparently reflect medical students’ nature that do not change over time.